'Is it a mosque?' The Islamization of space explored through residents' everyday 'discursive assemblages'. Issue 1 (2nd January 2019) - Baker, Julius
ABSTRACT: This article examines the Islamization of suburban space in southeast England. Its microgeographies of racialization challenge binary either/or logic, favoured by 'mosque conflict' approaches and instead demonstrate how residents' negotiations are channelled through everyday both/and logic rooted in multiplicity and indeterminacy. A key element in negotiations is the 'sometimes quality' of the 'Islamic Centre' that allows it to be both a 'mosque' and 'not-a-mosque'. Moreover, each of the differently positioned residents shows uneven discursive capacities for identity, belonging and community in relation to the Islamization of suburban space, and each is afforded differential empowerment and capabilities under social discourses of 'multiculturalism' and 'tolerance'. In examining these microgeographies of racialization, this paper also extends representational accounts of lived experiences surrounding the Islamization of space by attending to affect, emotion and materiality. To do so, the notion of 'discursive assemblage' is developed.